2
$\begingroup$

Let $S$ be a minimal surface, and let $\gamma$ be a geodesic parametrized by arc length, with curvature $k$ and torsion $\tau$,show that in the points of $\gamma$

$$ -K=k^2+\tau^2, $$

where, $K$ is the Gaussian curvature of $S$.

In this one I don't really know how to start, I thought about using $k^2=k^2_g+k^2_n$, or try to use the parametrization by asymptotic curves, but this took me nowhere.

$\endgroup$
3
  • 1
    $\begingroup$ The expression "parametrized by arclength" can only be applied to a curve rather than a surface. Furthermore curvature $k$ and torsion $\tau$ are defined for a curve rather than a surface. It's not clear what you are asking. $\endgroup$ – Mikhail Katz Jan 21 '16 at 17:12
  • $\begingroup$ Please give book/report reference to this question. The question can make sense with reference to a curve property selected on a surface specified, like in special cases $ K = \tau_g^2 + \kappa_n^2 $ etc. $\endgroup$ – Narasimham Jan 21 '16 at 18:19
  • $\begingroup$ Thank you for pointing it out, sorry for such a silly mistake, it is now corrected. $\endgroup$ – Kernel Jan 21 '16 at 18:30
1
$\begingroup$

First recall the relation of the three fundamental forms of a surface $S$ in $\mathbb{R}^3$: $$III-2HII+KI=0,$$ where $K$ and $H$ are the Gaussian and the mean curvature respectively. Since $S$ is minimal we obtain $$III+KI=0.$$ By evaluating along the geodesic $c\colon I\subset\mathbb{R}\longrightarrow S$, (parametrized by arclength) we obtain \begin{equation} III_{c(s)}(c'(s))+K(c(s))I_{c(s)}(c'(s))=0,\ \ \forall s\in I. \ \ \ (\dagger) \end{equation} But,

  • $I_{c(s)}(c'(c)):=||c'(s)||^2=1,\ \forall s\in I$, &
  • $III_{c(s)}(c'(s)):=I_{(N\circ c)(s)}((N\circ c)'(s))=||(N\circ c)'(s)||^2,\ \forall s\in I$, where $N$ is the Gauss map of $S$.
    Substituting to equation $(\dagger)$ we obtain $$-K(c(s))=||(N\circ c)'(s)||^2,\ \forall s\in I.\ \ \ \ (\ddagger)$$ Now, recall that $c$ is a geodesic. Therefore along $c$ the unit normal $N\circ c$ is parallel to the first normal of the curve $c$. Thus, $$(N\circ c)(s)=\pm \vec{n}(s),\ \forall s\in I.$$ By differentiating we obtain $$(N\circ c)'(s)=\pm(-k(s)\vec{t}(s)+\tau(s)\vec{b}(s)).$$ (Here we used the Frenet equation: $$\vec{n}'(s)=-k(s)\vec{t}(s)+\tau(s)\vec{b}(s),$$ where $\vec{t}(s)=c'(s), \vec{b}(s)$ is the second normal of $c$ and $k(s),\tau(s)$ are the curvature and the torsion of $c$ respectively.) Now, the desired result follows directly from the last equation and $(\ddagger)$, i.e. $$-K(c(s))=k^2(s)+\tau^2(s).$$
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.